Carcass and carcass cuts of F1 crossbred chickens of Pelung x Kampung given diets varied in protein content - Iskandar, Sofjan; Resnawati, Hety; Zainuddin, Desmayati (Indonesian Journal of Animal and Veterinary Sciences, 1999)
Observation on carcass and carcass cuts of F1 crossbred of Pelung x Kampung chickens influenced by dietary protein (15%, 17%, 19%, and 21% crude protein=CP) was carried out at the Research Institute for Animal Production, Ciawi Bogor. There were 360-day-old chicks of the crossbred, allocated to 9 dietary-protein treatments. The treatments were P1 (21%-17% CP), which was the ration with 21% CP given to chicks aged of 0-6 weeks, then continued with 17% CP ration up to 12 week of age; P2 was 21%-15% CP; P3 was 19%-19% CP; P4 was 19%-17% CP; P5 was 19%-15% CP; P6 was 17%-17% CP; P7 was 17%- 15% CP; P8 was 15%-19% CP and P9 was 15%-15% CP. At 6 and 12 weeks of age each two out of 10 birds per cage were randomly picked for carcass and carcass portion analysis. Results showed that carcass and wings of 6 weeks of age birds were not significantly (P>0.05) influenced by dietary protein, whilst breast and thighs & drumsticks were significantly (P<0.05) lower on lower dietary protein. The weight of carcass and carcass parts were 256, 58, 71, 32, 44, 8.6, 9.7 and 2.09 g/bird, for carcass, breast, thighs and drumsticks, wings, oval; liver, gizzard and abdominal fat, respectively. At 12 weeks of age, weight of carcass and carcass cuts were not affected by dietary protein. The weight of carcass and carcass cuts of 12 weeks of age were 803, 189, 251, 102, 123, 20, 25 and 21 g/bird, for carcass, breast, thighs and drumsticks, wings, oval, liver, gizzard and abdominal fat, respectively. The results indicated that ration with 15% CP given up to 12 weeks of age was recommended to be optimum without any reduction in carcass quality. Â  Key words: F1 crossbred of Pelung x Kampung chickens, dietary protein, carcass and carcass cuts